ABILITY OF ISOLATE PROBIOTIC BACTERIA CANDIDATE FROM KAKAP PUTIH (Lates calcarifer) IN PRESSING GROWING OF BACTERI Vibrio alginolyticus IN CO-CULTURE - Christine M Situmeang; Nursyirwani '; Irwan Effendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Three candidates of probiotic bacteria isolated from kakap putih (Lates calcarifer) had been examined for their antagonism against Vibrio alginolyticus. However, the ability to suppress the pathogen in co-culture system has not been tested. This research aimed to test the ability of probiotic candidates to suppress the growth of V. alginolyticus in co-culture trial. Three probiotics candidates (KP1, KP2, and KP3) were used in this experiment method. Four treatments consisted of P1 (broth culture of KP1 + V. alginolyticus), P2 (KP2 + V. alginolyticus ), P3 (KP3 + V. alginolyticus), P4 (V. alginolyticus) as control were prepared in triplicate. Total counts of each probiotic candidate and V. alginolyticus was calculated after 48 hours culture incubation. KP1 isolate showed highest ability suppress the growth of V. alginolyticus, followed by KP3 and KP2 isolates.Keywords: Probiotics, Kakap Putih, Growth, V. alginolyticus, Co-culture